Testing and characterization of durian seed flour filled polypropylene or high density polyethylene composites - Muhammad Haniff Zakaria (School of Materials Engineering, Universiti Malaysia Perlis, 2010)
The primary objectives: i- To investigate the physical properties of the DSF regarding particle size, surface area, density and thermal analysis; ii- To determine optimum filler content of durian seed flour in PP or HDPE composites. The filler content variability was chosen as 0, 10, 20, 30 and 40 php; iii- To study the effects or compatibilizer in the durian seed flour filled PP / HDPE comosites using maleic anhydride polypropylene (MAPP); iv- To investigate the ability of durian seed flour to be hybrid with other reinforcing fillers such as CaCO3 and corn starch. This evaluation is to achieve a superior balance of the composites properties and to minimize the use of more expensive fillers; v- To characterize the processing torque, FTIR, mechanical, thermal, morphological properties of the durian seed flour filled PP or HDPE composites.